Efektivitas dan Peningkatan Sekolah Konteks Intelektual dan Kebijakan - Wiwik Wijayanti (Fakultas Ilmu Pendidikan UNY, 2011)
The fact that effectiveness research found its ongtns in the phenomenon of the inefectiveness school. If school were really perfect, fulfilling their missions to the great satisfaction on pupils, parents, school board and politicians at local and national level, nobody would ever have wanted to start a process of school improvement with' teachers .through convicing them that improving their own performance is the right thing to do. School effectiveness needs a diftnition.because the concept is not altogether clear. We cannot just look at the output of the black box caledl 'school'; we also have to measure the input into it. Because we have to deal with a very complex entity, we need indicators or factors that can be compared and, even when we have school effectiveness factors, it still is difficult to know whether we are looking at causes or needs to be based on facts and figures derivedfrom a substantial number of school, which suggests the usually quantitative approach of school t;ffectiveness. Keywords: Effectiveness, improvement